2018
DOI: 10.1371/journal.pntd.0006502
|View full text |Cite
|
Sign up to set email alerts
|

Ts-Hsp70 induces protective immunity against Trichinella spiralis infection in mouse by activating dendritic cells through TLR2 and TLR4

Abstract: BackgroundTrichinellosis is a serious food-borne parasitic zoonosis worldwide. In the effort to develop vaccine against Trichinella infection, we have identified Trichinella spiralis Heat shock protein 70 (Ts-Hsp70) elicits partial protective immunity against T. spiralis infection via activating dendritic cells (DCs) in our previous study. This study aims to investigate whether DCs were activated by Ts-Hsp70 through TLR2 and/or TLR4 pathways.Methods and findingsAfter blocking with anti-TLR2 and TLR4 antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
(57 reference statements)
2
16
0
Order By: Relevance
“…Hsp70 has been previously described to influence innate immunity and inflammatory responses. 293 It has been believed that hepatocyte is devoid of innate immunities. Ma et al reported that the expression of Grp78 is stimulated by HBV replication.…”
Section: The Function Of Hsp70 Family In Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsp70 has been previously described to influence innate immunity and inflammatory responses. 293 It has been believed that hepatocyte is devoid of innate immunities. Ma et al reported that the expression of Grp78 is stimulated by HBV replication.…”
Section: The Function Of Hsp70 Family In Virus Infectionmentioning
confidence: 99%
“…299 Aside from the anti-inflammation function of intracellular Hsp70, the secreted extracellular Hsp70 binds to dendritic cells and macrophages before being recognized by its binding elements, most of which are innate immune receptors. 293,300 Toll-like receptors (TLRs) detect virus invasion and immediately trigger intracellular innate antiviral response. 301 They belong to type I integral membrane glycoproteins of IL-1 receptor (IL-1R) superfamily.…”
Section: The Function Of Hsp70 Family In Virus Infectionmentioning
confidence: 99%
“…Intestinal adult worms were collected at 7 dpi, and muscle larvae were recovered and counted at 35 dpi as previously described [27]. The protective immunity was calculated based on the percent of reduction in the mean number of adult worms or the recovered muscle larvae per gram (LPG) of muscle from vaccinated groups compared with PBS group.…”
Section: Parasite Burden Assessmentsmentioning
confidence: 99%
“…WT and NLRP3 −/− mice were infected with 300 muscle larvae (ML). MLs were recovered and counted at 35 dpi as previously described [16]. Briefly, the muscle tissues of infected mice were cut into pieces and digested by pepsin hydrochloric digestive fluid.…”
Section: Larvae Burden Assessmentsmentioning
confidence: 99%